Psychological Abuse in Jurisprudence Associated with Cults and Manipulative Groups: A Transcultural Study on Five Convictions - La Gamma, Martina; Bardavío Antón, Carlos; Velasco, Judith; Flores, Pilar; Rodríguez, Reyes; Moyano, Manuel (Journal of Aggression, Maltreatment & Trauma, 2024)
Groups of Psychological Abuse (GPAs) are hierarchical groups made up of one or several leaders and members who persistently and systematically use manipulative and coercive strategies to subjugate other people. The general aims of this study were (1) to obtain evidence of psychological abuse through the analysis of five sectarian cases and (2) to provide support for the taxonomy proposed by Rodríguez-Carballeira et al. (2015). An abductive content analysis extracted indicators from five case studies using court transcripts as secondary data sources. Results revealed 26 psychological abuse strategies, with the most prevalent category being control of personal life (41.9%), followed by emotional abuse (14.9%), and control and manipulation of information (14.7%). The most frequently used strategies of abuse were control over sexual life and emotional relationships, control-weakening of the psychophysical state, and manipulation of information. These findings suggest implications for prevention and intervention in both the psychological and legal context.
Keywords: coercive persuasion; cults; groups of psychological abuse; psychological manipulation; sects; sentences